THE FUNDAMENTAL CONCEPTIONAL PRINCIPLES OF ECONOMIC INTEGRATION IN THE CENTRAL ASIAN COUNTRIES - KURGANBAEVA, Gulmira (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Central Asian countries are actively participating in many development processes known today as globalization: as international trade expands, the number and volume of financial transactions in-crease, and investment flows intensify, states are integrating at a faster rate into the global economy. Developed countries have been elaborating their strategy for integrating into the global economy for decades now, constantly reassessing their vision of where they belong in this process. In contrast to them, the Central Asian republics are at the initial stage of entry into the global processes. Globalization challenges national economies, on the one hand, in particular their sustainability, while providing states with new opportunities, on the other. All of these challenges must be responded to, for globalization, which is based on intensification of the division of labor and the development of high technology, is an objective process not one of the world’s nations can afford to ignore (or become artificially isolated from).